2017
DOI: 10.1016/j.pnpbp.2017.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-7 nicotinic agonists for cognitive deficits in neuropsychiatric disorders: A translational meta-analysis of rodent and human studies

Abstract: Cognitive dysfunction in schizophrenia (SCZ) and Alzheimer’s disease (AD) is a major driver of functional disability but is largely unresponsive to current therapeutics. Animal models of cognitive dysfunction relevant to both disorders suggest the α7 nicotinic acetylcholine receptor (nAChR) may be a promising drug development target, with multiple clinical trials subsequently testing this hypothesis in individuals with SCZ and AD. However, the translational value of rodent cognitive tasks for predicting the ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 49 publications
0
50
0
Order By: Relevance
“…Selected drugs show some degree of cognitive improvement in trials of patients with schizophrenia, although none has yet proceeded to late phase or FDA approval. A common trend is the improvement of cognition with an inverted U-shaped dose-response curve, when increasing the dose of α7 agonist above a threshold resulted in loss of drug effect (Wallace and Bertrand, 2015;Lewis et al, 2017). The latest research has revealed a new generation of promising α7-targeting drugs (Beinat et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Selected drugs show some degree of cognitive improvement in trials of patients with schizophrenia, although none has yet proceeded to late phase or FDA approval. A common trend is the improvement of cognition with an inverted U-shaped dose-response curve, when increasing the dose of α7 agonist above a threshold resulted in loss of drug effect (Wallace and Bertrand, 2015;Lewis et al, 2017). The latest research has revealed a new generation of promising α7-targeting drugs (Beinat et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…There are still no effective approaches to prohibit the development and progression of schizophrenia. The available symptom-relieving compounds have ameliorated some sufferings of patients [ 21 , 22 ], however, drug development is still restricted by the unknown mechanisms of schizophrenia. A number of animal models have been established to investigate the mechanisms for schizophrenia, the cuprizone model uses the application of a chemical compound (cuprizone) to model schizophrenia-like symptoms [ 12 , 23 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several molecules are currently under test but α7 receptor-based therapies might yield less promising results than their M1 counterparts. In general, it must be recognized that recent clinical trials with cholinergic compounds have been disappointing at the level of efficiency on cognitive symptoms as well as undesirable side effects (Lewis et al, 2017;McArthur et al, 2010). This certainly emphasizes that we need a better understanding of the translational gap for therapeutics targeting nicotinic and muscarinic receptors.…”
Section: Nicotinic Receptorsmentioning
confidence: 99%